Bird’s Nest Fungi: Charismatic Mushrooms in Your Garden - Nattapol Kraisitudomsook; Matthew E. Smith (EDIS)
The “bird’s nest” fungi (Nidulariaceae) are charismatic mushrooms that look like small nests containing multiple tiny eggs. Because the ecological role of bird’s nest fungi is to decompose wood, they are extremely common in disturbed areas with plant debris and mulch, such as trails and backyard gardens. These fungi tend to grow in large clusters, so it is common to see ten to a hundred of these “nests” at once. Bird’s nest fungi are not considered dangerous to plants, animals, or humans. This new 3-page publication of the UF/IFAS Plant Pathology Department was written by Nattapol Kraisitudomsook and Matthew E. Smith. https://edis.ifas.ufl.edu/pp361